True Agreement Between India and Pakistan Regarding Disputes for The Kashmir Territory (International Journal of Scientific Research and Management (IJSRM), 2024)
Kashmir is an area located around the Himalayas which is located in northern India and Pakistan. Kashmir has been a trigger for conflict between India and Pakistan as both countries claim the Himalayan region. India and Pakistan have fought two wars over the Kashmir region, namely the India-Pakistan War in 1947 and the Kargil War in 1999. In 2019 tensions between India and Pakistan flared up again after India revoked the autonomy of the state of Jammu and Kashmir. The military leadership of India and Pakistan in February 2021 announced a truce agreement along the disputed border region in Kashmir. This was done after the exchange of fire between the militaries of the two countries in recent months.